Quarkonium production in pp and heavy-ion collisions - Song Taesoo; Aichelin Joerg; Zhao Jiaxing; Gossiaux Pol B.; Bratkovskaya Elena (EPJ Web of Conferences)
Campus Frankfurt, 60438 Frankfurt, Germany Abstract. We describe quarkonium production in pp and heavy-ion collisions by using the Remler’s formalism where quarkonium density operator is applied to all possible combination of heavy quark and heavy antiquark pairs. In pp collisions heavy (anti)quark momentum is provided by the PYTHIA event generator after rescaling pT and rapidity to imitate the FONLL calculations. Then spatial separation between heavy quark and heavy antiquark is introduced based on the uncertainty principle. In heavy-ion collisions quarkonium wavefunction changes with temperature assuming heavy quark potential equals the free energy of heavy quark pair in heat bath. The density operator is updated whenever heavy quark or heavy antiquark scatters in quark-gluon plasma (QGP). Our results are consistent with the experimental data on bottomonia from ALICE and CMS Collaborations assuming that the interaction rate of bottom (anti)quark in bottomonium is suppressed to 10 % that of unbound bottom (anti)quark. We also find that off-diagonal recombination of bottomonium from two different initial pairs barely happens even in Pb+Pb collisions at √sNN = 5.02 TeV.